PENGELOLAAN GURU SD - Ruhim Ruhim Ruhim (Manajer Pendididikan, 2016)
This study was to describe the management of teachers at State Primary School 4 North Curup Rejang Lebong District. This research used qualitative descriptive method. Planning needsof teachers has been done by analyzing the shortage of  eachers, with the involvement of the board teachers alone. Recruitment procedures can not be done because of the intervention of the local government. Coaching and development has been done in spite of its still modest. Beluampositively motivating nothing is done, it only needs to always be excited in the line of duty. Displacement (mutations) that are already done Roling teaching duties. Supervision andassessment has been carried out by means of diaries and classroom supervision. Dismissal has been done especially for civil servants who have retired and for tenga honorary who resigned.Keywords: management, teachers